Role of GeneXpert in Diagnosis of Covid-19 Among Armed Forces Personnel of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Bangladesh is one of the several countries which have successfully faced the challenge of recent Covid-19 pandemic. After the first emergence of the outbreak of SARS-CoV-2 virus in China, it rapidly spread over the whole world. From the very beginning of the pandemic, Bangladesh government has taken all sorts of effective measures to save millions of lives. In the perspective of the Covid-19 situations in Bangladesh Armed Forces, AFIP Dhaka Cantonment has still been contributing very successfully to combat this situation. By December 2020, Covid-19 laboratories of AFIP performed 90,495 RT-PCR tests and 15,595 were found positive. Besides RT-PCR tests another very sensitive and rapid method named GeneXpert is being used to provide the Covid-19 test reports within 1 hour. By using this GeneXpert test system AFIP immensely helped the patients who require emergency treatment intervention, for dead bodies requires immediate religious rituals, personnel who needs urgent reports to go overseas and also for VIPs and VVIPs in situations of urgency. For the last 1 year during this pandemic, AFIP has been providing the Covid-19 diagnostic facilities with utmost accuracy and quality of the tests. It is the honour and pride of this renowned and prestigious institution to render its continuous service in the critical period of our nation.J Bangladesh Coll Phys Surg 2022; 40: 78-83